Retrospective analysis of malaria prevalence over ten years (2015–2024) at Bichena Primary Hospital, Amhara Region, Ethiopia - Awoke Minwuyelet; Delenasaw Yewhalaw; Getnet Atenafu (PLoS ONE, 2025)
Background Malaria remains a significant public health challenge in Ethiopia, hindering the country’s productivity and development. While malaria incidence had decreased by 2018, and Ethiopia is working towards eliminating the disease by 2030, outbreaks still occur even in areas of low endemicity. Therefore the aim of this study was to assess the ten-year trend in malaria prevalence from 2015 to 2024 at Bichena Primary Hospital in the Amhara region of northwestern Ethiopia. Materials and methods A retrospective review of malaria blood film examination results was conducted using laboratory registration logbooks at Bichena Primary Hospital. Data collection was carried out from December 30, to January 14. The data were collected using a data collection sheet and entered into the Statistical Package for Social Sciences (SPSS) version for analysis. Bi-variable and multi-variable regression analyses and Pearson’s chi-square test were used to examine associations and differences in malaria prevalence trends across factors such as sex, age, year, and season and Plasmodium species. Descriptive statistics were also used to summarize the sociodemographic characteristics of the study participants and the results were presented in graphs, tables and texts. Results Out of the 24,107 malaria blood films examined, 4,322 (17.9%, 95% CI: 17.4%-18.4%) tested positive for Plasmodium infections. Of the confirmed cases, 58.7% were P. vivax, 28.6% were P. falciparum, and 12.2% were mixed infections. P. vivax was the predominant species throughout the study period (2015-2024), except for the years 2016 and 2018, when P. falciparum was more prevalent. Subsequently, an increase in malaria cases was reported, with the highest proportion recorded in 2024 (26.8%) and the lowest in 2018 (4%). The likelihood of malaria prevalence was 1.28 times higher in males than in females. Additionally, the chance of malaria prevalence was 1.27 times higher in the 15-24 age group compared to other age groups. The study revealed a significant rise in malaria prevalence, highlighting that malaria remains a major public health issue in the study area. There were also pronounced seasonal variations in malaria cases each year, with males and younger adults being more affected than females, older age groups, and children under five. Conclusions and recommendations Malaria prevention and control efforts need to be strengthened, focusing on regional differences. Ongoing research on diagnostic challenges, parasite elimination, and mosquito infectivity after malaria treatment is essential.